Effect of delaying insemination in beef heifers not expressing estrus by 48 hours after a 7-d CO-Synch plus controlled internal drug release timed artificial insemination protocol - Alexander, Dayna C. (Kansas State University, 2016)
Synchronizing estrus before AI is an effective way to shorten the breeding season, and increasing the number of pregnancies per AI may lead to greater use and acceptance of synchronization protocols among beef producers. Our objective was to determine if pregnancy rates to fixed-time AI (FTAI) would be improved by delaying insemination in heifers not expressing estrus before FTAI in a 7-d CO-Synch + controlled internal drug release (CIDR) estrus-synchronization protocol. In Experiment 1, yearling beef heifers (n = 465) at three locations of commercial and purebred herds were treated with GnRH (Cystorelin 100 µg im) and a CIDR insert (1.38 g of progesterone) on Day 0. On Day 7 CIDR inserts were removed and all heifers received PGF[subscript]2α (Lutalyse 25 mg im) and were fitted with an estrus-detection patch (Estrotect; Rockway, Inc.). Heifers were assigned to three treatments based on estrus-detection patch color at 48 h after PGF[subscript]2α: (1). Estrus-Red 48 h (Red 48; n = 180), heifers that expressed estrus and were inseminated at 48 h; (2). Non-Estrus-Gray 48 h (Gray 48; n = 137) heifers that did not express estrus and were inseminated at 48 h; and (3). Non-Estrus Delayed- 56 h (Gray 56; n = 148), heifers that did not express estrus at 48 h, and were not inseminated until 56 h after PGF[subscript]2α. Pregnancy rate to AI was greatest (P < 0.0001) for Red 48 heifers (67.8%) compared with heifers in the Gray 48 (39.4%) and Gray 56 (42.6%) treatments. Heifers assigned to Gray 48 and Gray 56 achieved similar (P = 0.83) pregnancy rates. In Experiment 2, yearling beef heifers (n = 257) at two different locations were treated with the same 7-d CO-Synch protocol, but heifers were assigned to three different treatments based on estrus-detection patch color at 48 h after PGF[subscript]2α: (1). Estrus-Red 48 h (Red 48; n =95), heifers that expressed estrus and were inseminated at 48 h; (2). Non-Estrus-Gray 48 h (Gray 48; n = 84), heifers that did not express estrus but were inseminated at 48 h; and (3). Non-Estrus Delayed- 72 h (Gray 72; n = 78), heifers that did not express estrus at 48 h, and were not inseminated until 72 h after PGF[subscript]2α. Pregnancy rate to AI was greatest (P = 0.004) for Red 48 heifers (62.1%) compared with heifers in Gray 48 (40.5%), and Gray 72 (46.2%). No difference in pregnancy rates (P = 0.75) was detected between heifers assigned to treatments Gray 48 and Gray 72. Delaying insemination in heifers not expressing estrus by 48 h after PGF[subscript]2α did not improve pregnancy rates to AI.
Keywords: Artificial insemination; Beef heifer; Estrous synchronization